2007
DOI: 10.14411/eje.2007.006
|View full text |Cite
|
Sign up to set email alerts
|

Variation, selection and heritability of thermal reaction norms for juvenile growth in Orchesella cincta (Collembola: Entomobryidae)

Abstract: Abstract. Genetic variation for thermal plasticity plays an important role in the success or failure of a species with respect to the colonization of different thermal habitats and the ability to deal with climatic change. The aim of this paper is to study the relative contribution of the additive and non-additive components of genetic variation for the slope of the temperature reaction norm for juvenile growth rate in the springtail Orchesella cincta. We present the outcome of an artificial selection experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…Moreover, it has also been widely documented in laboratory studies of responses to environmental temperature and water availability (e.g. Bennett et al 1992, Cavicchi et al 1995, Bull et al 2000, Gibbs et al 2003, Bubliy & Loeschcke 2005, Driessen et al 2007, Sørensen et al 2007, Vera et al 2008.…”
Section: Potential and Realized Evolution During Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has also been widely documented in laboratory studies of responses to environmental temperature and water availability (e.g. Bennett et al 1992, Cavicchi et al 1995, Bull et al 2000, Gibbs et al 2003, Bubliy & Loeschcke 2005, Driessen et al 2007, Sørensen et al 2007, Vera et al 2008.…”
Section: Potential and Realized Evolution During Climate Changementioning
confidence: 99%
“…Plastic changes have an underlying genetic basis and the extent of plasticity may thus also evolve (Scheiner 2002, Driessen et al 2007). For example, Nussey et al (2005) showed that great tits Parus major in the Netherlands have increased their phenotypic plasticity to cope with more unpredictable spring weather in the Netherlands over the last 32 yr.…”
Section: Potential and Realized Evolution During Climate Changementioning
confidence: 99%
“…Each line was initiated by one parental pair from a mass-bred population that had been cultured in the laboratory for 5 generations (Driessen et al 2007). The mass-bred population initially consisted of a mix of 4 populations: Poland (Pilica: 50°29.1' N, 19°39.6' E), Sweden (Ringarum: 58°21.5' N, 16°13.7' E) and The Netherlands (Roggebotzand: 52°34.4' N, 05°47.9' E; Amsterdamse Waterleidingduinen: 52°1.5' N, 04°33.1' E).…”
Section: Animals and Inbreeding Of Populationsmentioning
confidence: 99%
“…The parameters w i and w m were fixed for all scenario's ( Table 1) and were derived from empirical data on growth curves and life history of Collembola, which show that individuals show exponential growth until reaching maturity after repeated moult cycles, after which growth rate slows down (Jansen & Joosse 1987;Ernsting & Isaaks 1997;Driessen et al 2007). Salinity of the habitat varies among simulations from nonsaline to saline conditions (S 0-10 ).…”
Section: Model Descriptionmentioning
confidence: 99%
“…A generalist response curve provides a constant growth rate independent of salinity. Exponential growth determines the body weight at time t according to w t+1 = w t · e r , and an individual reaches maturity if w t ≥ w m (Driessen et al 2007). A mature individual has a reproductive rate m of one surviving offspring per time step.…”
Section: Model Descriptionmentioning
confidence: 99%